Strategi dan implementasi manajemen risiko operasional pada perbankan syariah - Khotimah, Husnul (Maliki Interdisciplinary Journal, 2025)
This study examines the strategy and implementation of operational risk management in Islamic banks with a focus on identifying, measuring, monitoring, and controlling risks. Islamic banking in Indonesia faces complex challenges in managing operational risks that include internal process failures, human error, system disruptions, and external risks. The main challenges include the complexity of sharia contracts, limited human resources, and cyber threats due to technological advances. Islamic banks’ efforts in dealing with operational risk include the implementation of technology, employee training, and internal controls. With a proactive approach, Islamic banks can increase customer confidence and ensure operational sustainability.